Genetically encoded Ca2+ indicators: molecular scale measurements in mammals in vivo - Kotlikoff, Michael I. (Henry Stewart Talks, 2013)
Calcium Signaling, How to study complex biology, Genetically encoded Ca2+ indicators, GcaMPs, Structural basis of Ca2+ sensing, Lineage specification of indicators in transgenic mice, Real-time cardiac activation, Response time considerations, Heart development, Cell based therapy and coupling, Embryonic stem cells and GCaMPs, Vascular control and pulsars, Future directions
Archived at 2020/08/13